Cellular Prion Protein (PrPc) and Hypoxia: True to Each Other in Good Times and in Bad, in Sickness, and in Health - Ramljak, Sanja; Herlyn, Holger; Zerr, Inga (Frontiers in Cellular Neuroscience, 2016)
The cellular prion protein (PrPc) and hypoxia appear to be tightly intertwined. Beneficial effects of PrPc on neuronal survival under hypoxic conditions such as focal cerebral ischemia are strongly supported. Conversely, increasing evidence indicates detrimental effects of increased PrPc expression on cancer progression, another condition accompanied by low oxygen tensions. A switch between anaerobic and aerobic metabolism characterizes both conditions. A cellular process that might unite both is glycolysis. Putative role of PrPc in stimulation of glycolysis in times of need is indeed thought provoking. A significance of astrocytic PrPc expression for neuronal survival under hypoxic conditions and possible association of PrPc with the astrocyte-neuron lactate shuttle (ANLS) is considered. We posit PrPc-induced lactate production via transactivation of lactate dehydrogenase A by hypoxia inducible factor 1α as an important factor for survival of both neurons and tumor cells in hypoxic microenvironment. Concomitantly, we discuss a cross-talk between Wnt/ß-catenin and PI-3K/Akt signaling pathways in executing PrPc-induced activation of glycolysis. Finally, we would like to emphasize that we see a great potential in joining expertise from both fields, neuroscience and cancer research in revealing the mechanisms underlying hypoxia-related pathologies. PrPc may prove focal point for future research.